Locality and socio-cultural elements in Li Tianbao's works - Chung, Sook Peng (2015)
A work reflects and refracts the identity of the author to a certain extent. The theme,language, ideology and interaction with different ethnicity culture incorporated in Li Tian-bao’s works have a strong sense of local elements. These elements constitute the “place” connotation in the works. Therefore, the ‘place’ connotation of works should not be overlooked or simply been played down. Previous researchers focused on the ‘Chinese-ness’ of Li’s fictional work. Less attention was given to his “place” connotation and the scholars considered his works as “diasporic writings”. This study applied the theory of “production of locality” of an anthropologist, Arjun Appadurai,and the theory of “local practices of anti-diaspora” of Shih Shu-mei to review Li’s fictional works. The former elaborates the ‘production of locality’ in Li’s fictional works specifically. The latter discusses if the “place connotation” was being ignored intentionally or unintentionally, and categorized his works as diasporic writing. This thesis attempts to explain and encompasses aspects such as social and cultural traditions, cuisine and memorial ceremonies. to achieve social integration, . As for the local history, Li Tian-bao deals with the memories of traumatic events among the Chinese community and enriches the connotation of his localized subject matters by means of fragmented narrative structure. The researcher believes by using the argument of ‘source’ and ‘stream’ in Shi Shu-mei can further sort out the complexities of ‘Chinese-ness’ and diaspora in Li’s writings. The diasporic journey may end and the southbound Chinese immigrants may reside permanently and start a family here. They have actually chosen to put an end to their diasporic status from the very beginning. Li’s works has provided an appropriate footnote.